Deteksi Stunting pada Anak Prasekolah dan Pelatihan Pemantauan Pertumbuhan Anak: Upaya Mewujudkan Generasi Emas Tahun 2045 - Zakiah, Mistika; Ulfah, Ridha; Asseggaf, Syarifah Nurul Yanti Rizki Syahab; Putri, Triyana Harlia (Pakis Journal Institute, 2026)
Indonesia is the country with the second highest prevalence of stunting in children under five in Southeast Asia, which in 2022 reached 31.8%. Preschool-age children are one of the groups of children at high risk of stunting. One strategy to overcome nutrition problems is to increase teachers' knowledge about the importance of health checks for students. Community service will be held at the Al-Mumtaz IT Kindergarten in Pontianak Kota District in October. The target is teachers and students. All teachers of Al-Mumtaz IT Kindergarten will receive training in stunting detection and education. The procedures for this community service activity are divided into several stages, namely checking the weight and height of students and analyzing the prevalence of stunting, training for teachers in detecting stunting; and providing stunting education to all teachers of Al-Mumtaz IT Kindergarten. Training activities will be carried out in the form of educational video presentations, interactive lectures and stunting early detection examination practices which begin with a pretest and end with a posttest. Then the data will be collected and articles will be made that will be published in the PKM journal, besides that a video of the implementation of the activity will also be made and published in the online media.